Combination of chemically modified SDF‐1α mRNA and small skin improves wound healing in diabetic rats with full‐thickness skin defects. Issue 12 (6th August 2022) - Luo, Zucheng; Bian, Yujie; Zheng, Rui; Song, Yonghuan; Shi, Li; Xu, Haiting; Wang, Huijing; Li, Xiaoyan; Tao, Zhenyu; Wang, Anyuan; Liu, Ke; Fu, Wei; et al.
Abstract: Objectives: Diabetes mellitus is associated with refractory wound healing, yet current therapies are insufficient to accelerate the process of healing. Recent studies have indicated chemically modified mRNA (modRNA) as a promising therapeutic intervention. The present study aimed to explore the efficacy of small skin engineered to express modified mRNAs encoding the stromal cell‐derived factor‐1α (SDF‐1α) facilitating wound healing in a full‐thickness skin defect rat model. This study, devised therapeutic strategies for diabetic wounds by pre‐treating small skin with SDF‐1α modRNA. Materials and Methods: The in vitro transfection efficiency was evaluated using fluorescence microscopy and the content of SDF‐1α in the medium was determined using ELISA after the transfection of SDF‐1α into the small skin. To evaluate the effect of SDF‐1α modRNA and transplantation of the small skin cells on wound healing, an in vivo full‐thickness skin defect rat model was assessed. Results: The results revealed that a modRNA carrying SDF‐1α provided potent wound healing in the small skin lesions reducing reduced scar thickness and greater angiogenesis (CD31) in the subcutaneous layer. The SDF‐1α cytokines were significantly secreted by the small skin after transfection in vitro. Conclusions: This study demonstrated the benefits of employing small skin combined with SDF‐1α modRNA in enhancing wound healing in diabetic rats having full‐thickness skin defects. Abstract : An illustration of how the small skin was transfected with the SDF‐1α modRNA and the design of the in vivo experiments.